Portrait of Deradicalization in Indonesia: Has Pancasila Been Considered Effective? - Febriansyah, Johan (Indonesian Journal of Counter Terrorism and National Security, 2022)
In discussing this journal, we will discuss Pancasila values ​​related to deradicalization so that the understanding of radicalism in Indonesia can be reduced. Cases of radicalism in Indonesia itself have been increasing lately, this can be proven by the existence of news reports about terrorists carrying out their actions and also the number of suspected terrorists who have been arrested by the police. This happened because radicalism began to spread rapidly and many people did not apply Pancasila values ​​in the life of society, nation and state. The lack of public understanding of Pancasila values ​​and a weak attitude of nationalism has resulted in increased incidents of violence, persecution and radical acts in the name of religion. Therefore, the government must always be active in eradicating radicalism and deradicalization in order to create a harmonious, peaceful, safe and secure life in our beloved homeland.